SERVICE QUALITY AND CUSTOMER SATISFACTION IN THE APICULTURE-BASED AGRITOURISM - Gandhy, Abel; Chang , Michael; Rahmi , Siti (Jurnal Organisasi dan Manajemen, 2019)
Taman Wisata Lebah is tourism service based on honey bees. It is one of the pioneer of the apitourism in Indonesia. The objective of this reserach are to analyze the service quality and customer satisfaction of Taman Wisata Lebah. Research method used in this research is quantitative. Respondent in this research are 100 respondents, using purposive sampling technique. Data analysis techniques are Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). Based on the calculation of CSI, the number is indicated that in general consumers of Taman Wisata Lebah are satisfied with the services provided. Findings. Based on the calculation of Importance Performance Analysis, there are five attributes with high importance and low performance and highly recomended to improve. The atributes consists of provide more safety equipment for customers, evaluate staff shifting schedule to ensure the existence of staff in field, improvement product knowledge for field staff, create safety box for bee colony. Overall, service quality in Taman Wisata Lebah is excellent.